Healthcare IT Innovations: Blockchain Technology for Healthcare Data Security and Privacy - Vikas Gopal Jha; Omkar Gupta (International Journal of Information Security Engineering, 2025)
The healthcare sector has undergone a significant digital transformation, leading to the generation and sharing of vast quantities of sensitive medical data. While this digitization has improved patient care and outcomes, it has also introduced critical challenges related to data security and privacy. The increasing rate of data breaches in healthcare puts patient confidentiality at risk, mainly leading to identity theft, financial fraud, and loss of public trust in healthcare systems. These breaches not only compromise the integrity of healthcare organizations but also expose systemic vulnerabilities in how sensitive information is stored and managed. Besides this, the trend of shifting to digital platforms has increased the level of complexity involved in complying with strict data protection regulations, which complicates the health care sector’s ability to ensure the security of patient information. These issues highlight the imperative need for strong solutions that can ensure the protection of sensitive medical information while being in compliance with changing data protection regulations. Blockchain technology, because of its decentralized, immutable, and transparent architecture, presents a very promising framework to address these issues. Unlike traditional centralized systems, blockchain provides a distributed ledger that can securely store and share medical records without the risk of single points of failure. This decentralized approach ensures that patient data remains tamper-proof and accessible only to authorized parties, significantly enhancing privacy and reducing the risk of fraud. In addition, blockchain technology streamlines healthcare operations by automating processes such as claims management, billing, and access permissions through smart contracts. These capabilities not only reduce administrative overhead but also bring about greater transparency and accountability among healthcare stakeholders. The integration of blockchain into the healthcare ecosystem can empower patients with greater control over their data, allowing for a more patient-centric approach to care. This study examines the transformative potential of blockchain in healthcare, looking at its applications, benefits, and challenges while outlining future directions toward improving data security and privacy.
Keywords: Data Security; Healthcare; blockchain; data breaches; patient privacy